Design and bioactivity evaluation of a novel autotaxin inhibitor with anti-hepatic fibrosis effects - Yuzheng Liu; Dan Luo; Hongwen Leng; Chaolun Gu; Qingrong Ding; Lin Zhao; Xinxin Chao; Hanxia Wang; Yueteng He; Silu Zhu; Guanhua Ai; Weijie Peng (Scientific Reports)
Abstract Autotaxin (ATX) is considered as a serum marker of hepatic fibrosis, which is positively correlated with the degree of hepatic fibrosis. However, there are no clinical studies on anti-hepatic fibrosis drugs targeting ATX. This study attempts to find novel ATX small molecule inhibitors based on virtual screening methods including two-dimensional similarity search, pharmacophore screening, molecular docking, drug-like properties and ADMET filtration, combined with biological evaluation. An ATX inhibitor (IC50 = 43.05 µmol/L) is discovered by our screening strategy. In vivo result show that the novel ATX inhibitor represents excellent anti-hepatic fibrosis effects in mice. This screening strategy had potential significance for the discovery of ATX inhibitors in the future.